Clinicians' involvement in data collection for portfolio research: impact on their clinical practice and perception of research. (2nd June 2020) - Sweeting, David; Daniell, Helena; Chester, Rachel
Abstract : Background/Aims: Physiotherapists generally have a positive view of research, but have identified a number of barriers to taking part, and have expressed challenges when attempting to integrate research findings into their practice. The aim of this study was to describe the self-reported impact of collecting data for a multicentre research study on physiotherapists' clinical practice. Methods: Convenience sampling was used to select three of 11 NHS trusts involved in the original data collection. A questionnaire was emailed to the 28 of 34 physiotherapists working within these three Trusts who collected data and for whom contact details were available. Results: A total of 21 (75%) physiotherapists completed the questionnaire. Out of the 21 physiotherapists, 15 stated they were aware of the study results; all of whom reported subsequent changes in their beliefs about prognostic factors for shoulder pain (subject of the original study) and some alteration in clinical practice. However, barriers to integrating further changes into practice were reported, including lack of time and a perception that patients would not engage with a more (bio)psychosocial approach. Overall, 85% of responders stated data collection had changed their understanding of the research process. Conclusions: Clinicians' participation in the research process positively influenced practice. However, 29% were unaware of the results and only 33% of physiotherapists accessed the published article. There were perceived barriers to integrating results into practice.